« Faire de la place. » Les migrants européens aisés et la transformation du quartier Solvay (Bruxelles) - Charlotte Casier (Territoire en Mouvement)
This study examined the contribution of wealthy migrants to the social transformation of urban territories, analysing the processes and agents that facilitate the settlement of that specific social group in certain neighbourhoods. The results are based on a field survey conducted between February and June 2018 by qualitative methods in the Brussels Solvay neighbourhood. Solvay is located east of the Brussels inner ring and near Matonge, the popular Congolese commercial centre. Since 2000 it has been internationalising and upgrading because of the settlement of a large population of wealthy Europeans, attracted by the international functions of Brussels and the institutions of the European Union. This case-study demonstrates that the arrival of this high-income group is linked to the production of "ready-to-use" spaces for the latter by a multitude of economic agents, by the redevelopment of public space, the construction of a trendy commercial offer and the development of new segments of the real estate market, reflecting a generalized gentrification of the district. Real estate and commercial actors thus benefit from this solvent public, present in the short term and with particular consumption patterns. The public authorities support or even anticipate this transformation. It ousts the working classes of the area by the reduction in the supply of affordable housing, the creation of new commercial structures and policies to control urban space. In this way, the various agents who "make room" for wealthy Europeans in certain Brussels districts actively contribute to the transformation of the city.